Superior Hypogastric Plexus Block Successfully Treats Severe Penile Pain After Transurethral Resection of the Prostate. Issue 6 (November 1998) - Rosenberg, Samuel K.; Tewari, Rajiv; Boswell, Mark V.; Thompson, Gary A.; Seftel, Allen D.
Abstract : Background and Objectives: Superior hypogastric plexus block has been used to treat cancer pain of the pelvis. Methods: A patient with severe chronic nonmalignant penile pain after transurethral resection of the prostate underwent a single superior hypogastric plexus block with local anesthetic and steroid. The patient was also started on medications that treat neuropathic pain a few hours after the procedure was finished. Results: The superior hypogastric plexus block resulted in complete pain relief immediately after the procedure. The pain relief continued at 1, 2, 4, and 8 months follow up. Conclusions: In this case of severe penile pain the superior hypogastric plexus block was useful diagnostically and therapeutically.